XDA Developers' Android hacker's toolkit : the complete guide to rooting, ROMs and theming - Tyler, Jason, 1976- (John Wiley & Sons, 2012)
Make your Android device truly your ownAre you eager to make your Android device your own but you're not sure where to start? Then this is the book for you. XDA is the world's most popular resource for Android hacking enthusiasts, and a huge community has grown around customizing Android devices with XDA. XDA's Android Hacker's Toolkit gives you the tools you need to customize your devices by hacking or rooting the android operating system. Providing a solid understanding of the internal workings of the Android operating system, this book walks you through the terminology and functions of the android operating system from the major nodes of the file system to basic OS operations. As you learn the fundamentals of Android hacking that can be used regardless of any new releases, you'll discover exciting ways to take complete control over your device. Teaches theory, preparation and practice, and understanding of the OSExplains the distinction between ROMing and themingProvides step-by-step instructions for Droid, Xoom, Galaxy Tab, LG Optimus, and more Identifies the right tools for various jobs Contains new models enabling you to root and customize your phoneOffers incomparable information that has been tried and tested by the amazing XDA community of hackers, gadgeteers, and techniciansXDA's Android Hacker's Toolkit is a simple, one-stop resource on hacking techniques for beginners.